Infectious bronchitis-virus-like QX strain transmission, pathogenesis, replication, and host miRNA biogenesis pathway hijacking mechanism - Khan, Asad; Khan, Iftikhar Ali; Huang, Chao; Luo, Qihui; Qadeer, Abdul; Jia, Lanlan; Aboul-Soud, Mourad A. M.; Alkubaisi, Noorah A.; Chen, Zhengli (Frontiers in Cellular and Infection Microbiology, 2025)
The infectious bronchitis virus (IBV) is an acute, highly contagious, single-stranded RNA (ssRNA) gammacoronavirus mainly transmitted to chickens through the intranasal route. Positive-sense ssRNA viruses primarily act on mRNA and enhance the replication of viral copies. We identified the nasal entry site of the IBV-QX strain and provided insights into the minimal viral replication in systemic organs. Here is an overview of its entry mechanisms and tropism in systemic organ tissues. It enters the host cells via spike proteins, which bind to highly expressed receptors in respiratory, renal, and gastric epithelial cells. Viral RNA primarily replicates in the host cell environment, where it is directly translated into viral proteins. The precise replication of the IBV-QX strain in gastric epithelial cells was previously unknown. Different IBV strains have varying tropism. For the first time, we revealed the key players involved in the microRNA (miRNA) biogenesis pathway by transfecting gastric cells with the IBV-QX strain. Our findings suggest that the QX strain may bind to angiotensin-converting enzyme-2 (ACE2) receptors by circulating throughout the lymphatic system at the very least and influence the translation of argonaute2 (AGO2), Dicer, exportin5 (XPO5), and Drosha proteins. Taken together, QX viral proteins disrupt host miRNA biogenesis, leading to dysregulated immune and cellular responses that enhance viral replication and systemic spread, thereby enabling cross-organ tropism and multi-system pathogenesis.